2006
DOI: 10.1016/j.crma.2006.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Linear theory of wave generation by a moving bottom

Abstract: The computation of long wave propagation through the ocean obviously depends on the initial condition. When the waves are generated by a moving bottom, a traditional approach consists in translating the 'frozen' sea bed deformation to the free surface and propagating it. The present study shows the differences between the classical approach (passive generation) and the active generation where the bottom motion is included. The analytical solutions presented here exhibit some of the drawbacks of passive generat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 4 publications
1
60
0
Order By: Relevance
“…While the first crest is very similar for the two dispersive simulations, we clearly observe effects of the over-representation of shorter-wave components in the former solution in the trailing crests. In a corresponding study Dutykh et al (2006) found larger differences for the leading crest, since they made the comparison at a much earlier time. The dispersion time, τ , in the figure is close to 0.5, the limit where dispersion effects should be taken into account according to Kajiura (1963).…”
Section: Indmentioning
confidence: 99%
“…While the first crest is very similar for the two dispersive simulations, we clearly observe effects of the over-representation of shorter-wave components in the former solution in the trailing crests. In a corresponding study Dutykh et al (2006) found larger differences for the leading crest, since they made the comparison at a much earlier time. The dispersion time, τ , in the figure is close to 0.5, the limit where dispersion effects should be taken into account according to Kajiura (1963).…”
Section: Indmentioning
confidence: 99%
“…This is why it is valid to use the linearized water-wave equations. Dutykh et al (2006) and others showed that taking an instantaneous seabed deformation is not equivalent to instantaneously transferring the seabed deformation to the ocean surface, except in the framework of the linearized SWEs (very long waves). The difference comes from the vertical velocities and dispersion.…”
Section: Energy In the Framework Of The Dispersive Linearized Equationsmentioning
confidence: 99%
“…While the common practice in modelling tsunami generation consists in translating the initial sea bottom deformation to the water surface, thus neglecting all dynamical effects, we prefer to include some dynamics in the process in an effort to be closer to what happens in reality (Dutykh et al 2006). We construct the bottom motion by multiplying Okada's static solution z à OK ðx à ; y Ã Þ 1 by a function of time (Hammack 1973),…”
Section: Simulations Of Energymentioning
confidence: 99%
“…More precisely, we will investigate two cases of slow and fast uplifts of a portion of bottom. This simple situation has some important implications to tsunami genesis problems [23,33,58]. The physical domain and discretization parameters are inherited from the last section.…”
Section: Wave Generation By Sudden Bottom Upliftmentioning
confidence: 99%